Study of microwave drying of vegetables by numerical modeling : Influence of dielectric properties and operating conditions - Arballo, Javier Ramiro (2018)
In the present work mass and energy transfer during microwave dehydration of vegetables were studied. Microwaves interact with the polar molecules of food enabling its heating and dehydration. This interaction is affected by the change of the food properties due to temperature increase and water content reduction. In certain products, the dependence of dielectric properties with temperature is affected by a change in the food structure as a consequence of the chemical change of certain components and the water loss. Lambert´s law, that considers an exponential decay of incident microwave power, was applied to model these interactions. Additionally, two consecutive stages must be considered: initial heating followed by intensive evaporation at constant temperature. The model was successfully validated for data published in literature related to slabs of microwave dehydrated potatoes and carrots, considering different processing times, power densities, pressure and sample size.